Effect of low‐pressure cold plasma processing on decontamination and quality attributes of Saffron (Crocus sativus L.). Issue 6 (14th March 2022) - Darvish, Haleh; Ramezan, Yousef; Khani, Mohammad Reza; Kamkari, Amir
Abstract: This study investigated the microbial decontamination of saffron using the low‐pressure cold plasma (LPCP) technology. Therefore, other quality characteristics of saffron that create the color, taste, and aroma have also been studied. The highest microbial log reduction was observed at 110 W for 30 min. Total viable count (TVC), coliforms, molds, and yeasts log reduction were equal to 3.52, 4.62, 2.38, and 4.12 log CFU (colony‐forming units)/g, respectively. The lowest decimal reduction times (D‐values) were observed at 110 W, which were 9.01, 3.29, 4.17, and 8.93 min for TVC, coliforms, molds, and yeasts. LPCP treatment caused a significant increase in the product's color parameters (L*, a*, b*, ΔE, chroma, and hue angle). The results indicated that the LPCP darkened the treated stigma's color. Also, it reduced picrocrocin, safranal, and crocin in treated samples compared to the untreated control sample ( p < .05). However, after examining these metabolites and comparing them with saffron‐related ISO standards, all treated and control samples were good. Abstract : Saffron was treated by radiofrequency (RF) low‐pressure cold plasma (LPCP). Higher input powers and exposure times efficiently reduced the microbial load. All saffron color parameters significantly increased in treated samples, and LPCP significantly decreased saffron's҆ secondary metabolites.